대학 교양영어수업에서의 협동학습의 효과에 대한 연구 - 성창섭; 정영숙; 성기완 (영어교육연구, 16(4), 2004)
This study investigates differences in students’ achievement among the traditional, cooperative, the web-based cooperative learning groups, students’ attitudes and opinions about the general English courses, and the strengths and weaknesses of the cooperative learning. This study conducted in two provincial universities involves 5 teachers and 254 students. The data were collected through the achievement tests, student surveys, class observations, teachers’ journal, and focus group interviews. The primary findings are 1) no statistically significant differences were found in the final exams among the three groups in each school even though statistically significant differences on the mid-term exams were found between the traditional and cooperative learning groups in both schools, and the cooperative and web-based learning groups in School B, and 2) while the students in the cooperative class engaged in active class participation, those in the web-based cooperative group used the Internet and web-based technology more in and after class, and 3) the web-based group appeared to be more teacher-controlled. Some practical ways of engaging in meaningful practices by utilizing cooperative learning principles in the context of general English courses are also discussed. KCI Citation Count: 6